Matrix Gla Protein expression pattern in the early avian embryo - Correia, Elizabeth (2016)
MGP (Matrix Gla Protein) is an extracellular matrix vitamin K dependent protein previously identified as a physiological inhibitor of calcification and shown to be well conserved among vertebrates during evolution. MGP is involved in other mechanisms such as TGF-beta and BMP activity, and a proposed modulator of cell-matrix interactions. MGP is expressed early in vertebrate development although its role has not been clarified. Previous work in the chicken embryo found MGP localization predominantly in the aorta and aortic valve base, but no data is available earlier in development. Here we examined MGP expression pattern using whole-mount in situ hybridization and histological sectioning during the initial stages of chick development. MGP was first detected at HH10 in the head and in the forming dorsal aorta. At the moment of the onset of blood circulation, MGP was expressed additionally in the venous plexus which will remodel into the vitelline arteries. By E2.25, it is clear that the vitelline arteries are MGP positive. MGP expression progresses centrifugally throughout the area vasculosa of the yolk sac. Between stages HH17 and HH19 MGP is seen in the dorsal aorta, heart, notochord, nephric duct, roof plate, vitelline arteries and in the yolk sac, beneath main arterial branches and in the vicinity of several vessels and venules. MGP expression persists in these areas at least until E4.5. These data suggest that MGP expression could be associated with cell migration and differentiation and to the onset of angiogenesis in the developing chick embryo. This data has biomedical relevance by pointing to the potential use of chick embryo explants to study molecules involved in artery calcification.